Architectural parallels between biological and engineered solutions in defence and security. Issue 1 (13th September 2016) - Smith, Gary Robert; Daniel‐Allegro, Brigitte
Abstract: Bio‐mimetics have often provided a useful means of inspiration for engineering design – for instance in fabrication of materials for aerospace. One more recent area of interest, from the perspective of cyber security has been in the remarkable ability of the immune system to cope with the diversity and evolution of threats such as bacteria and viruses. The focus of this paper is to further examine the architectural parallels between biological systems and engineered solutions in defence and security. Systems thinking and modelling are the tools utilized in examining the architectures and the capabilities of the biological systems such as anticipatory, adaptability and self‐respect. In performing such an examination, it is anticipated that insight and potential improvements may be found in both directions – improvements in our approaches to combat complex disease and also possible inspiration in the science, architectures and designs for our engineered systems.